The effects of airblast on sheep in two-man foxholes - Richmond, Donald R.; Jones, Robert K.; Fletcher, E. R.; Lovelace Foundation for Medical Education and Research.; United States. (Lovelace Foundation for Medical Education and Research, 1971)
The blast effects in rectangular two-man foxholes were evaluated using sheep. There were two open foxholes at ground ranges of 560, 650, 830, 940, and 1,300 feet from a 500-ton TNT charge. Because of an anomalous detonation, pressures measured adjacent to the foxhole layout were significantly below those predicted. Moreover, luminous jets emanating from the fireball produced shock waves that preceded the main shock. This gave rise to a blast wave with double shocks known generally to be less damaging to biological systems. All the sheep survived the blast. At the 560- and 650-foot ranges (37 and 21 p.s.i.) some of the sheep sustained slight amounts of pulmonary hemorrhage. In addition, they exhibited a high incidence of eardrum rupture of a severe form. (Author).
"1 June 1971."
Includes bibliographical references (page 23)
The blast effects in rectangular two-man foxholes were evaluated using sheep. There were two open foxholes at ground ranges of 560, 650, 830, 940, and 1,300 feet from a 500-ton TNT charge. Because of an anomalous detonation, pressures measured adjacent to the foxhole layout were significantly below those predicted. Moreover, luminous jets emanating from the fireball produced shock waves that preceded the main shock. This gave rise to a blast wave with double shocks known generally to be less damaging to biological systems. All the sheep survived the blast. At the 560- and 650-foot ranges (37 and 21 p.s.i.) some of the sheep sustained slight amounts of pulmonary hemorrhage. In addition, they exhibited a high incidence of eardrum rupture of a severe form. (Author).
Keywords: Atomic bomb / Blast effect. / http://id.loc.gov/authorities/subjects/sh85009311; Blast effect. / http://id.loc.gov/authorities/subjects/sh85014788